2005
DOI: 10.1088/1009-1963/14/5/006
|View full text |Cite
|
Sign up to set email alerts
|

Controlled quantum teleportation and secure direct communication

Abstract: We present a controlled quantum teleportation protocol. In the protocol, quantum information of an unknown state of a 2-level particle is faithfully transmitted from a sender (Alice) to a remote receiver (Bob) via an initially shared triplet of entangled particles under the control of the supervisor Charlie. The distributed entangled particles shared by Alice, Bob and Charlie function as a quantum information channel for faithful transmission. We also propose a controlled and secure direct communication scheme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In the teleportation protocol proposed in the paper [23]. A sender, Alice, successfully transmits an unknown state of a two-level particle to a remote receiver, Bob.…”
Section: Related Workmentioning
confidence: 99%
“…In the teleportation protocol proposed in the paper [23]. A sender, Alice, successfully transmits an unknown state of a two-level particle to a remote receiver, Bob.…”
Section: Related Workmentioning
confidence: 99%
“…Subsequently, several theorists and experimenters have discussed, analysed and reported on this kind of quantum communication. For the later, Ting et al [13], proposed a controlled and secure quantum teleportation of a 2-level particle via an initially shared triplet of entangled particles under the control of the supervisor Charlie. Chen et al [14], suggested a quantum teleportation protocol between multiple senders and multiple receivers via only one supervisor Charlie, where the supervisor shares the entangled state with every sender, while there is no directly shared entanglement between sender and receiver.…”
Section: Introductionmentioning
confidence: 99%
“…The essence here is that two different types of states are exchanged between the two parties. Controlled quantum communication protocols appeared in works by Liu et al [35], Gao et al [36], Zhang et al [37], Choudhury et al [38], etc. The role of the Controller is to oversee the protocol as a whole and, after getting satisfied, perform certain actions leading to the completion of the protocol.…”
Section: Introductionmentioning
confidence: 99%